Evaluasi Pelaksanaan Peraturan KPU No 13 Tahun 2020 Di Kabupaten Serdang Bedagai pada Pemilihan Bupati dan Wakil Bupati Tahun 2020 - Muhammad Riski Fadly Sitorus; Adam Adam; Isnaini Isnaini (Universitas Medan Area, 2025)
This research evaluates the implementation of Regional Head Elections (Pilkada) in Indonesia during the COVID-19 pandemic. The pandemic's entry impacted the originally scheduled general elections, which were initially planned for September 23, 2020, but were postponed to December 9, 2020. In response to the pandemic, the General Election Commission (KPU) issued Regulation 13 of 2020 as an adaptation measure. The study employed a qualitative approach with direct observation as the data source. This research aims to evaluate the implementation of the Pilkada by KPU Regulation No. 13 of 2020 and identify potential risks of virus transmission. The study also examines the challenges in KPU's socialization process to the public and candidates during the Pilkada 2020. Activities such as voter education, public participation, and socialization were carried out through various methods, primarily using online media due to limitations in face-to-face socialization to comply with health protocols. The research findings indicate that Pilkada campaigns faced violations of health protocols, which require serious attention to prevent the further spread of the COVID-19 virus. Therefore, innovations are needed in the Pilkada process during the pandemic to ensure the safety and well-being of the community.